IMPLEMENTATION EVALUATION AND FEASIBILITY OF DEVELOPMENT OF NEW ENERGY OF MINI COAL GASIFICATION ON MICRO, SMALL, AND MEDIUM ENTERPRISES - Dasryanto, Dasryanto; Purwanto, Budi (Jurnal Aplikasi Manajemen, 2017)
Resource and Development Center for Mineral and Coal Technology conducts research on the development of mini gasifier from laboratory scale to the pilot project. The activity from 2015 such as the Implementation of tree units of Mini Gasifiers, which each had the capacity of 10-15 kg/hour on Tofu Micro, Small, And Medium Enterprises, a capacity of 30 kg/hour on Atsiri Oil and Capacity of 50 kg/hour on Aluminum Smelter. Determination of IE Matrix strategy position was based on total value of IFE, which was given point on the X axis and total value of EFE Matrix on Y axis. The total value of IFE Matrix was 2.581 and EFE Matrix was 2.868. Therefore, user position of Mini Gasifier was placed on V cell, which was protecting and defending. The corresponding strategy to be applied on this cell was market penetration and product development. The identification result from strengths, weakness, opportunities, and the threat of capacity as well as quantity and quality on Micro, Small, And Medium Enterprises on V cell, next would be used to formula alternative strategy by using SWOT matrix. Based on SWOT analysis from some alternative strategies those have been formulated, chosen strategy priority to be applied product capacity using quantity as well as quality on Micro, Small, and Medium Enterprise accordance with production capacity using quantity as well as quality on supporting and implementing protecting and defending strategies. From joint QSP matrix estimation, the result was to implement Mini Gasifier energy technology utilization by adapting marketing demand and era development with the highest power trail among other alternative strategies for 7.2. Based on QSPM with the expertise from Mini Gasifier user, came with two strategies with same value (7.0) became strategy priority was production capacity development strategy with ease to obtain raw material of coal on Micro, Small, And Medium Enterprises and strategy of Mini Gasifier energy technology implementation with adapting market demand and era development. QSPM analysis with expertise from Distributor that produced two strategies with the same value (7.0), which was the strategy of transformation management implementation in facing the dynamic of human resource management quality in the absorbing process of Mini Gasifier technology and utilization strategy of Mini Gasifier energy technology with adapting market demand and era development.